Seepage failure of a foundation pit with confined aquifer layers and its reconstruction. (August 2022) - Xu, Xiao Bing; Hu, Qi; Huang, Tian Ming; Chen, Yun; Shen, Wen Ming; Hu, Min Yun
Highlights: A seepage failure in a foundation pit with underlying confined aquifer layers is investigated. The performance of remedial works for the reconstruction of the foundation pit is discussed. The suggestions for controlling seepage risks of deep soil excavation projects are given. Abstract: Seepage control is one of the key issues for the design and construction of deep soil excavation projects. A seepage failure occurred around an abandoned pile in a foundation pit with confined aquifer layers, and caused damages to the retaining wall and support system and surrounding environment. The causes of the accident are analyzed, and the reconstruction of the project are introduced. The seepage failure was attributed to the defects in the three-axis mixing piles and the potential weak region created around the abandoned pile. It was finally controlled by filling the whole foundation pit with water. A systematic reinforcement of the foundation pit was carried out. The soil disturbed by the seepage failure was reinforced by two-shot process grouting and sleeve valve pipe grouting. The cast-in-place piles and prestressed assembled steel struts were constructed to strengthen the original retaining wall and support system. An ultra-deep (61.5 m) trench-cutting re-mixing deep wall (TRD) was successfully constructed in complex stratum, and showed good waterproof performance through a pumping test. After the formal dewatering inside the foundation pit by three stages, the project was successfully finished. This study could provide a wealth of experience and guidance for the design and construction of future similar deep excavation projects.